Práctica de los valores en la educación - Herrera Villacís, Maryuri Lizbeth (2016)
The practice of values in education is an issue of great relevance, however Education Unit Guasaganda no studies or previous research that clearly shows the importance of this problem of integrating learning intentionally and consciously, meaning not only think about the content as knowledge and skills, but the relationship they have within society. In this research process using methodological guidelines on practices suggested values, to thereby harmonize the educational processes aimed at respect and rules of conduct, in addition to optimize learning in the academic activities of teachers and students. techniques were used as interviews and surveys of teachers, students, and parents, whose results were that the property does not have strategies to guide the teacher in the implementation or practice of values, aspects as important to quality education warmth; also he diagnosed that teachers are not adequately trained in this field of knowledge; finally a proposal that involves the training of teachers through the development of a methodological guide that included exercises based on the development of social behavior was established.